Self-Esteem Hubungannya dengan Penyalahgunaan Narkotika dan Obat-obatan Berbahaya pada Siswa SMK Negeri 2 Batu Malang - Bagus Hayu Adhi Pradhana (Universitas Kanjuruhan Malang, 2015)
Self-esteem is an essential human need for survival and normal, healthy development. Self-esteem refers to feelings such as whether individuals can receive a success or failure, how many efforts have been done , whether failure would be painful or not, and whether the individual will be able to as a result of the experiences suffered. Abuse of narcotics and dangerous drugs among teenagers today, one reason because it has a prestige that is too high. The subjects were students SMK Negeri 2 Batu. This study aims to determine the level of self-esteem students of SMK Negeri 2 Batu and the relationship between self-esteem with the abuse of narcotics and dangerous drugs to students at SMK Negeri 2 Batu. This research use descriptive correlational with cluster random sampling. Research instrument used questionnaire and data were processed using percentage and product moment. These studies (1) identify of self-esteem 38.06%, in high, 56.72% in medium criteria, and 5.22% in low. (2) correlation coefficient r xy = 0.957 at significant level of 0.05. It can be concluded that there is a relationship or a significant positive correlation between self-esteem with the abuse of narcotics and dangerous drugs.